Esther in Dura Europos: Ancient Jewish Memories of Achaemenid Persia 4 - Middlemas, Jill; Ben Zvi, Ehud (Journal of Hebrew Scriptures, 2025)
Location matters, and this article explores the depiction and significance of the Esther/Mordecai (Purim) panel's placement next to the Torah niche in the Dura Europos Synagogue. It aims to answer questions such as what the visual representation may have conveyed and which memories the panel might have evoked by its presence in that particular place. To address these questions, the article probes the historical, visual, and ideological context of the panel within the Jewish synagogue in the mid-third century CE. It shows how the local Jewish population engaged with the depiction of Esther and Mordecai, not only as Diaspora heroes, but also as figures linked to Jewish memory, identity, and resistance in a Roman-Persian borderland. In doing so, it showcases how visual media in antiquity served Jewish communities in constructing sacred memory, connecting past and future hopes, and asserting their cultural identity in imperial contexts. In addition, it presents a fresh analysis of the legacy of the by then long-defunct Achaemenid Empire and its enduring presence in the memories, imagination, and minds of Jews living at the crossroads of the Parthian and Roman Empires.